2013
DOI: 10.1007/s00408-013-9494-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bag Volume on Reproducibility of Inert Gas Rebreathing Pulmonary Blood Flow Measurements in Patients with Pulmonary Diseases

Abstract: V bag can be altered between 1,200 and 2,200 ml in most situations without affecting the reproducibility. Attention has to be paid to extreme volumes in obstructive patients. Nevertheless, V bag should be chosen as large as possible and therefore has to be carefully adapted, particularly in patients with obstruction or restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This may be due to the increased breathing frequency required, which increases oxygen demand from respiratory muscles and in turn increases cardiac output [18]. Other studies have reported an underestimation of cardiac output by the N 2 O rebreathing technique compared to other techniques at rest and during exercise [36,37], with > 30 % of recorded values lower than what was considered possible [39]. This is possibly due to recirculation of N 2 O [20], which could reduce the alveolar-arterial diffusion gradient for N 2 O and attenuate further N2O uptake [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to the increased breathing frequency required, which increases oxygen demand from respiratory muscles and in turn increases cardiac output [18]. Other studies have reported an underestimation of cardiac output by the N 2 O rebreathing technique compared to other techniques at rest and during exercise [36,37], with > 30 % of recorded values lower than what was considered possible [39]. This is possibly due to recirculation of N 2 O [20], which could reduce the alveolar-arterial diffusion gradient for N 2 O and attenuate further N2O uptake [23].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac magnetic resonance imaging is currently accepted as the non-invasive gold standard method for cardiac output assessment [14,15]. However, this technique is expensive, time consuming and not applicable in daily practice [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation